Exploring Vitiligo History and Mental Health Burden Among People Within EU5 Countries: Findings from the Global VALIANT Study - Khaled Ezzedine; John E. Harris; Iltefat H. Hamzavi; Kristen Bibeau; Jessy Gao; Haobo Ren; Nanja van Geel (Dermatology and Therapy)
Abstract Introduction Vitiligo is a chronic autoimmune disease characterized by destruction of pigment-producing melanocytes in the skin. This study explores the patient and treatment history of vitiligo and associated mental health burden in EU5 countries. Methods The cross-sectional global Vitiligo and Life Impact Among International Communities (VALIANT) study recruited people with vitiligo via an online panel and surveyed them regarding clinical characteristics, vitiligo treatment, quality of life (QoL), and mental health. Results A total of 1151 patients were surveyed in EU5 countries (France, n = 250; Germany, n = 250; Italy, n = 200; Spain, n = 200; UK, n = 251). Half of patients (50.3%) reported a family history of vitiligo, with highest rates in France (66.4%) and Germany (58.8%). Many patients experienced flares during periods of stress (65.1%) or itching before/during a flare (61.5%), with highest rates in Germany (78.4%/78.8%, respectively; P < 0.01 vs all). German patients used the greatest mean number of vitiligo treatments (6.5; P < 0.0001 vs all), and French patients reported the highest rates of current non-treatment (20.8%; P < 0.05 vs Germany). Half of patients (53.9%) reported frequently hiding their vitiligo lesions, with highest rates in Germany (60.4%) and France (58.4%; both P < 0.05 vs Italy/Spain). German and French patients also reported highest disease burden (P < 0.05 vs Italy/Spain/UK). Over half (58.3%) of patients reported diagnosed mental health conditions (anxiety [26.5%]; depression [23.4%]). Rates of moderate to severe depressive symptoms were highest in Germany (64.8%; P < 0.05 vs all). Conclusion Among EU5 countries, patients from Germany and France generally reported higher burden than those from Italy, Spain, or the UK, although the impact of vitiligo on these patients cannot be discounted. Patients reported flares during periods of stress and great impact of vitiligo on their QoL and mental health. There is continued need for improved management strategies for patients with vitiligo, including the reduction of QoL and mental health burden. Graphical Abstract A graphical abstract is available for this article.